A Game-Theoretic Approach for the Synthesis of Complex Systems - Bruyère, Véronique (Revolutions and Revelations in Computability, 2022)
In this brief overview, we consider multi-player turn-based infinite-duration games that are played on a finite directed graph and such that each player aims at maximizing a payoff or minimizing a cost. We discuss several solution concepts and present some classical as well as some more recent results, with a focus on reachability objectives for the players.